2019
DOI: 10.1039/c9cc07517h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of interfacial passivation in inverted perovskite solar cells

Abstract: The crucial hierarchy of the interfacial passivation at different positions of perovskite solar cells together with the corresponding mechanism has been studied despite the selection of passivation mediums in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This hierarchy in interfacial passivation was attributed to the ''reparation'' effect of the utilized passivation medium on the perovskite layer, as it induced both ''interfacial'' and ''bulk'' effects by effectively filling the grain boundaries of the perovskite layer and reducing the trap state density in both the perovskite layer and the interface between it and the upper carrier transport layer. 168 A PCE of 19.55% and a V OC of 1.133 V with negligible hysteresis and better long-term and thermal stability were achieved for the champion devices with an upper passivation layer of polystyrene (PS) or polymethyl methacrylate (PMMA). Moreover, an ultrathin passivation layer consisting of a PMMA:PCBM mixture was highly effective in passivating interfacial defects near the perovskite/TiO 2 interface, significantly suppressing interfacial recombination.…”
Section: Polymer Induced Passivationmentioning
confidence: 99%
“…This hierarchy in interfacial passivation was attributed to the ''reparation'' effect of the utilized passivation medium on the perovskite layer, as it induced both ''interfacial'' and ''bulk'' effects by effectively filling the grain boundaries of the perovskite layer and reducing the trap state density in both the perovskite layer and the interface between it and the upper carrier transport layer. 168 A PCE of 19.55% and a V OC of 1.133 V with negligible hysteresis and better long-term and thermal stability were achieved for the champion devices with an upper passivation layer of polystyrene (PS) or polymethyl methacrylate (PMMA). Moreover, an ultrathin passivation layer consisting of a PMMA:PCBM mixture was highly effective in passivating interfacial defects near the perovskite/TiO 2 interface, significantly suppressing interfacial recombination.…”
Section: Polymer Induced Passivationmentioning
confidence: 99%
“…They found that passivation on the upper interface is generally more efficient than on the lower interface in inverted PSCs. In the end, the highest PCE of 19.55 % was achieved by using the upper interface passivation strategy [10] . In 2022, Li et al reported the 4‐[(trifluoromethyl) sulphonyl]‐aniline (4TA) with trifluoromethyl (−CF 3 ) and aniline (−NH 2 ) functional groups have strong interaction with Pb 2+ ions, which can suppress surface defects and delay crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…In the end, the highest PCE of 19.55 % was achieved by using the upper interface passivation strategy. [10] In 2022, Li et al reported the 4-[(trifluoromethyl) sulphonyl]-aniline (4TA) with trifluoromethyl (À CF 3 ) and aniline (À NH 2 ) functional groups have strong interaction with Pb 2+ ions, which can suppress surface defects and delay crystallization. The À CF 3 group can form a hydrophobic protective layer to prevent water invasion for perovskite film.…”
Section: Introductionmentioning
confidence: 99%